2015
DOI: 10.15407/spqeo18.02.209
|View full text |Cite
|
Sign up to set email alerts
|

Structure of photoluminescence DL-spectra and phase transformation in lightly doped SiC crystals and films

Abstract: Complex spectroscopic study of one-dimensional disordered structures caused by solid phase transformations in SiC crystals was presented. Disordered growth D-layers in lightly doped crystals and α-SiC films were investigated using low temperature photoluminescence. The analysis testifies that DL and SF spectra hand-in-hand follow the structure transformations. It has been shown that the DL and SF spectra of luminescence reflect the fundamental logic of SiC polytypes structure. This allows to observe the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Values of α are the same as in the case of DL i , for the same range of τ [8]. Also, there is a differentiated variation of the fine structure intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of α are the same as in the case of DL i , for the same range of τ [8]. Also, there is a differentiated variation of the fine structure intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental results and theoretical calculations showed that the luminescence of different polytypes strongly influenced by defects [1][2][3]. The luminescence spectra [4,5] of SiC crystals and films with stacking faults (SF i ) in highpurity SiC [2] and with deep level (DL i ) [6][7][8][9] in lightly doped SiC reflect formation of intermediate metastable phases during 3C↔6H transitions. SF i and DL i spectra hand-in-hand follow the structure transformations.…”
Section: Introductionmentioning
confidence: 99%
“…2). These electrical properties of the films obtained within the temperature range 200…600 °C are shown in Table. Formation of nc-SiC at the temperature 200 °C is confirmed by obtained electrophysical and X-ray data [4][5][6].…”
Section: Experiments and Discussionmentioning
confidence: 96%
“…Perfect nanocrystal shows a typical spectrum of nitrogen bound exciton complexes (PRS) together with the linear ABC-spectrum related to Ti [(δ-0) -(a)] and emission spectra of the donor-acceptor pairs. Another spectrum with zero-phonon line (2.89…2.94 eV) was found after identifying the SF [4] and DL spectra [5,6]. GB spectra were observed simultaneously with the SF and DL ones (Figs.…”
mentioning
confidence: 99%
“…P. 62-66. doi: 10.15407/spqeo19.01.062 10H 2 〈55〉, 14H 2 〈77〉) were studied in the work [8]. Defects in the lightly doped SiC crystal with grown defects of structure were studied in [9][10][11]. The deep-level (DL) spectra manifested itself the most clearly, emphatically and intensively in the case when strong diffuse scattering effects are present in the Laue diffraction pattern [11][12][13][14], after intercalation of the multilayer polytypes and layers with the disorder structure (single axis disorder), in SiC crystals and films with the impurity concentration of…”
Section: Introductionmentioning
confidence: 99%